2018
DOI: 10.1186/s12866-018-1366-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-3470b promotes bovine ephemeral fever virus replication via directly targeting mitochondrial antiviral signaling protein (MAVS) in baby hamster Syrian kidney cells

Abstract: BackgroundBovine ephemeral fever virus (BEFV), the causative agent of bovine ephemeral fever, is an economically important pathogen of cattle and water buffalo. MicroRNAs (miRNAs) are endogenous 21-23 nt small non-coding RNA molecules that binding to a multiple of target mRNAs and functioning in the regulation of viral replication including the miRNA-mediated antiviral defense. However, the reciprocal interaction between bovine ephemeral fever virus replication and host miRNAs still remain poorly understood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…CoV RNA can be recognized by RIG-I-like receptors (RLRs), including retinoic acid-inducible gene I (RIG-I) and/or melanoma differentiation gene 5 (MDA5), in the cytoplasm [ 19 ]. After activation, RIG-I and MDA5 can interact with the adapter mitochondrial antiviral signaling protein (MAVS, also termed IPS-1, VISA, and Cardif) [ 16 , 20 ]. Subsequently, MAVS recruits two IKK-related kinases, TANK-binding kinase 1 (TBK1) and inducible IκB kinase (IKKi), leading to activation of the transcription factors interferon regulatory factor 3/7 (IRF3/7) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…CoV RNA can be recognized by RIG-I-like receptors (RLRs), including retinoic acid-inducible gene I (RIG-I) and/or melanoma differentiation gene 5 (MDA5), in the cytoplasm [ 19 ]. After activation, RIG-I and MDA5 can interact with the adapter mitochondrial antiviral signaling protein (MAVS, also termed IPS-1, VISA, and Cardif) [ 16 , 20 ]. Subsequently, MAVS recruits two IKK-related kinases, TANK-binding kinase 1 (TBK1) and inducible IκB kinase (IKKi), leading to activation of the transcription factors interferon regulatory factor 3/7 (IRF3/7) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was found that these two miRNAs also downregulated some mitochondrial metabolism-related proteins and a solute carrier protein SCL-25 A-12, which can act on MAVS downstream, further destroying the antiviral immune response of mitochondria ( Yasukawa et al, 2020 ). Another miRNA (Mir-3470b) was upregulated after infection with bovine ephemeral fever virus (BEFV) and promoted viral replication by targeting MAVS to inhibit antiviral signal transduction ( Hou et al, 2018 ). In recent years, the regulation of miRNA has become a research hotspot, and literature has reported the induction or protection of miRNA during the occurrence of various diseases ( Du et al, 2019 ; Kumar et al, 2019 ), which suggests that different miRNAs may be the key targets for future treatment of various diseases.…”
Section: Viral Infection and Mitochondrial Dynamicsmentioning
confidence: 99%
“…reported that miR-3470b directly targets MAVS 3’-UTR in Bovine ephemeral fever virus infection. In that study, the authors discovered that the overexpression of miR-3470b resulted in a marked decrease in MAVS at both the transcriptional and protein levels, thereby suppressing the antiviral response ( 85 ). Further, miR-3570 negatively regulates rhabdovirus-triggered production of type I interferons by targeting MAVS in miiuy croaker macrophages, thus facilitating viral replication ( 86 ).…”
Section: Microrna-mediated Mavs Therapiesmentioning
confidence: 99%